A DIFFERENT SURGICAL TECHNIQUE FOR FINDING EMBEDDED LAD LOCALIZATION: "SEARCH TECHNIQUE WITH INCISIONS PERPENDICULAR TO THE LAD" - Unal, Mustafa; Tashmamatov, Md. Dr. Abdiashim; Nazarov, Md. Dr Asan Nazarov; Osmonov, Damirbek (Journal of Humanitarian Cardiovascular Medicine, 2025)
Performing an anastomosis to the desired location of the left anterior descending artery (LAD) is not always easy for cardiac surgeons. The techniques described to solve this problem have advantages and disadvantages. Low likelihood of complications and easy to repair if they occur; We believe that it is a technique that has a rapid learning curve, does not cause coronary intimal damage, does not require additional equipment, and is suitable for the morphology and physiology of the heart; We wanted to define the “LAD search method with vertical incisions”.